OVERLAP AXONAL POLYNEUROPATHY WITH IMMUNE MEDIATED NECROTISING MYOPATHY - Koh, Ewe Jin; Chin, Ming Lee; Ab’llah@Ariffin, Nor Aizan (Journal of Ayub Medical College Abbottabad, 2024)
Immune mediated necrotising myopathy (IMNM) is a rare autoimmune disease of the muscles belonging to the subset of the idiopathic inflammatory myopathies (IIM). This disease entity has classically been associated with myositis specific antibodies. The hallmark feature in clinching the diagnosis of IMNM would be a muscle biopsy showing muscle necrosis and regeneration in the absence of significant inflammatory infiltrates, interpreted in an appropriate clinical context. The term ’˜neuromyositis’ was previously coined in the year 1893 to describe a concomitant polyneuropathy in patients with polymyositis or dermatomyositis. However, a combined polyneuropathy with IMNM has never been reported in previous literature. We describe a case of a 35-year-old gentleman who presented with a 5-day history of symmetrical bilateral lower limb pain and weakness. Despite a negative autoimmune work-up, his muscle biopsy was suggestive of IMNM. A nerve conduction study done had also revealed a superimposed non-length dependant axonal polyneuropathy. The patient had responded well to steroids and is now under remission. This case serves to highlight a rare entity of seronegative IMNM superimposed with an axonal polyneuropathy.